ENHANCING PREGNANT WOMEN'S BREASTFEEDING SELF-EFFICACY THROUGH ANIMATED EDUCATIONAL VIDEO INTERVENTION - Aan Fitri Ries Sutrisno; Desi Trianita; Fransisca Retno Asih (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: The prevalence of exclusive breastfeeding remains low globally, with only 44% of infants receiving it during the first six months. One contributing factor is low Breastfeeding Self-Efficacy (BSE). In Indonesia, 56% of mothers have low BSE due to inadequate education, limited family support, and psychological challenges. Animated video-based education is considered effective in increasing BSE among pregnant women, potentially enhancing exclusive breastfeeding success. This study aimed to examine the effect of breastfeeding preparation education using animation videos on BSE in third-trimester pregnant women at Tanah Kalikedinding Public Health Center, Surabaya, in 2022. Method: A quasi-experimental design with a pretest-posttest and control group was used. Seventy-four pregnant women (37 per group) were selected through consecutive sampling and met inclusion criteria: gestational age 28–36 weeks, single healthy pregnancy, ability to use WhatsApp, Google Forms, and Zoom, and willingness to participate. Exclusion criteria included serious medical conditions or hearing/vision impairments. The intervention group received an animated video titled “Manfaat ASI dan Persiapan Menyusui” (5 minutes/day for 3 days), along with Q&A and video sharing. The control group was directed to read breastfeeding material from the KIA book. Data were analyzed using Mann-Whitney and Wilcoxon tests via SPSS25. Result: Results showed a significant increase in BSE in the intervention group (mean increase = 4.97) compared to a decrease in the control group (mean decrease = 2.49), with p = 0.000. Conclusion: In conclusion, animated video-based education effectively improves breastfeeding self-efficacy and may support the success of exclusive breastfeeding programs.